Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan di PT PLN (PERSERO) UP2B Jawa Timur - Lucia Dian Aprilisa; Emmywati (PUTRA JAWA PUBLISHER, 2023)
The purpose of this research is to find out whether leadership style has an influence on employee performance at PT PLN (Persero) UP2B East Java. This type of research is quantitative in nature and the data options that can be used are various primary data obtained through field visits directly to the object of the research objective. The work step in collecting data is by using a sample of thirty-seven (37) employees who work there by distributing questionnaires via the Google form. The data obtained was then processed using SPSS Version 27 and using Simple Linear Regression analysis, this is because in this study only used one independent variable. The analytical method used is in the form of instruments, namely validity and reliability tests, statistical tests and classical assumption tests which include tests for normality, multicollinearity, heteroscedasticity, and simple linear regression. From the output of the various tests, the results obtained are Fcount = 4,131, where the significance is 0.05 which is less than the standard, which is 0.05, so that the regression model can be used to predict the participation variable or the influence of the Leadership variable (X). to the employee performance variable (Y). As well as the test results which illustrate if the magnitude of the correlation value or relationship R is worth 0.325. So that through the output results obtained a coefficient of determination (Rsquare) worth 0.106, which means that if the influence of the independent variable (Leadership) on the dependent variable (Employee performance) with a value of 10.6%.